Progress with restoration and management of Eastern Suburbs Banksia Scrub on North Head, Sydney. (May 2015) - Lambert, Geoff; Lambert, Judy
<x xml:space="preserve">Abstract</x> How has management of Eastern Suburbs Banksia Scrub vegetation on North Head progressed over the last 6 years and what insights can be gained from recent treatments?